2011
DOI: 10.1016/j.njas.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding strategies, genotypes, sex, and birth weight on carcass and meat quality traits under organic pig production conditions

Abstract: a b s t r a c tNutrient supply in organic pig production is characterized by limited amino acids (AA) availability due to the preferable use of home-grown feedstuffs and restrictions on purchased feedstuffs. This can cause large variations in the quality of diets, carcasses, and pork. The objective of two feeding trials was to assess the interactions between feeding regimes, genotype, and birth weight on carcass and pork quality. A control regime was compared with two feeding regimes that were partly (only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
2
19
1
1
Order By: Relevance
“…Sundrum et al [29] and Brustolini and Fontes [30] showed that due to the lower feed intake, females require approximately six days extra to reach the slaughter weight of 120 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Sundrum et al [29] and Brustolini and Fontes [30] showed that due to the lower feed intake, females require approximately six days extra to reach the slaughter weight of 120 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Lower dietary CP and lysine concentrations have been associated with higher IMF in pork (Sundrum et al . ; Apple ; Urriola et al . ; Maeda et al .…”
Section: Resultsmentioning
confidence: 97%
“…Sundrum (2005) has reported that certain diets may increase the IMF of pork without affecting carcass BFT. Lower dietary CP and lysine concentrations have been associated with higher IMF in pork (Sundrum et al 2011;Apple 2013;Urriola et al 2013;Maeda et al 2014). Wu (1980) reported that N and ash concentrations of meat from pigs fed basal diets supplemented with sweet potato chips (0, 1% and 2% of BW) decreased, while ether extract and energy did not change.…”
Section: Muscle Compositionmentioning
confidence: 99%
“…They found that castrated males showed a worse FCR, 10.6% and 7.0% higher than intact males and females, respectively, confirming that castrated males develop greater feed intake; however, they have worse feed efficiency and less deposition of lean meat (Brustolini and Fontes, 2014). Although the females present better FCR compared with castrated males, recent studies have shown a DFI deficit for them, which requires an increase around six days to reach the same slaughter weight of males (Sundrum et al, 2011;Brustolini and Fontes, 2014).…”
Section: Discussionmentioning
confidence: 99%